Coping Behaviors and Psychological Disturbances in Youth Affected by the COVID-19 Health Crisis - Orgilés, Mireia; Morales, Alexandra; Delvecchio, Elisa; Francisco, Rita; Mazzeschi, Claudia; Pedro, Marta; Espada, José Pedro (Frontiers in Psychology, 2021)
The COVID-19 epidemic and the quarantine that children in many countries have had to undergo is a stressful situation about which little is known so far. The coping behaviors carried out by children and adolescents to face home confinement can be associated with their emotional welfare. The objectives of this study were: 1) to examine the coping strategies carried out by children and adolescents during the COVID-19 health crisis, 2) to analyze the differences in these behaviors in three countries, and 3) to examine the relationship between different modalities of coping and better adaptation. Participants were 1,480 parents of children aged 3-18 years from three European countries (n Spain = 431, n Italy = 712, and n Portugal = 355). The children’s mean age was 9.15 years (SD = 4.27). Parents completed an online survey providing information on symptoms and coping behaviors observed in their children. The most frequent coping strategies were accepting what is going on (58.9%), collaborating with quarantine social activities (e.g., drawings on the windows, supportive applauses) (35.9%), acting as if nothing is happening (35.5%), highlighting pros of being at home (35.1%), and not seeming worried about what is happening (30.1%). Compared to Italian and Spanish children, Portuguese children used a sense of humor more frequently when parents talked about the situation. Acting as if nothing happened, collaborating with social activities, and seeking comfort from others was more likely in Spanish children than in children from the other countries. Compared to Portuguese and Spanish children, those from Italy seem not worried about what was happening. Overall, an emotional-oriented coping style was directly correlated with a greater presence of anxious symptoms, as well as mood, sleep, behavioral, and cognitive alterations. Task-oriented and avoidance-oriented styles were related to better psychological adaptation, measured as the low presence of psychological symptoms. Results also show that unaffected children or children with a lower level of impact were more likely to use strategies based on a positive focus on the situation. This study provides interesting data on the strategies to be promoted by parents to cope with the COVID-19 health crisis in children.